The impact of the Central America free trade agreement on agriculture and the rural sector in five Central American countries: Executive summary - Jansen, Hans G. P.; Morley, Samuel; Torero, Máximo (International Food Policy Research Institute, 2007)
The International Food Policy and Research Institute (IFPRI), headquartered in Washington, D.C.and represented by an office in Central America based in RUTA, in San Jose, Costa Rica, and the Sub-regional Economic Commission for Central America (ECLAC) office based in Mexico, have been executing the Project on the Impact of the Central America Free Trade Agreement on Agriculture and the Rural Sector in Five Central American Countries (“the Project”). The Project covers the fi ve Central American countries (Guatemala, El Salvador, Honduras, Nicaragua and Costa Rica), and it is expected that its outputs serve as a guide on the type of policies and complementary measures that must be taken for the countries to maximize the use of the new economic environment brought about by CAFTA and, at the same time, reduce possible negative impacts that could take place among the vulnerable groups of the rural areas in these countries. The Project started with a qualitative analysis using economic sense to obtain criteria on courses and magnitudes of the effects of CAFTA on the welfare level of producers and consumers. However, the Project’s main activities have approached a series of quantitative analyses, namely: Analysis of CAFTA’s impacts on macroeconomic indicators (economic growth, employment, imports, exports, etc.), sector behavior, income distribution and poverty, through simulations with national mathematical models such as Calculated General Equilibrium (CGE) models. Analysis of fi ve productive chains affected by CAFTA in each of the fi ve countries, and which are relevant for the small producer, with emphasis on how the treaty will change competitiveness of each of these items and obstacles that hinder their competitiveness on imports or the use of new export opportunities. New opportunities that may arise for substitute import products that could face certain challenges, and for export items whose prospects could improve as a result of trade opening. Calculation of economic rates of return of public investments that improve access to various types of infrastructure (roads, electricity, drinkable water and telephones) on the basis of a cost-benefi t analysis, as an input for the design of complementary agendas. The purpose of this report is to provide a summary of the qualitative analysis outputs, and synthesize key results of the three types of quantitative analyses mentioned above..